Preparation and Magnetic Properties of Cobalt-Doped FeMn2O4 Spinel Nanoparticles - Aleksandr A. Spivakov (SpringerOpen, 2021)
Abstract Mixed-metal oxide nanoparticles have attracted great scientific interest since they find applications in many fields. However, the synthesis of size-controlled and composition-tuned mixed-metal oxide nanoparticles is a great challenge that complicates their study for practical application. In this study, Co-doped FeMn2O4 nanoparticles were synthesized by the solvothermal method in which the crystallization was carried out under autogenous pressure at temperatures of 190 °C for 24 h. The influence of Co doping on the evolution of the structural and magnetic properties was investigated by various methods. It was found from XRD data that crystallite size decreases from 9.1 to 4.4 nm with the increase in Co content, which is in good agreement with the results of TEM. Based on the results of magnetic measurements, it was found that the saturation magnetization first increases with an increase in the cobalt content and reaches its maximum value at x = 0.4, and a further increase in x leads to a decrease in the saturation magnetization. The influence of cation redistribution on the observed changes has been discussed.